ADDITIONS AND CORRECTIONS TO THE CLASSIFICATION OF WESTERN HEMISPHERE Epilachna (COLEOPTERA: COCCINELLIDAE) - GORDON, ROBERT D. (Revista Colombiana de Entomología, 1985)
Three new species, Epilachna rauli, E. madrigali, and E. pseudotumida are described; the homonymy Epilachna kraatzi Gordon and E. nana Gordon are replaced by E. colombiana, and E. minuta, new names, respectively. New host records are given for some species Epilachninae.